A Retrospective Study on the Protective Effects of Topical Vancomycin in Patients Undergoing Multilevel Spinal Fusion. Issue 1 (9th January 2016) - Gaviola, Marian L.; McMillian, Wesley D.; Ames, Suzanne Elizabeth; Endicott, Jeffrey A.; Alston, Wallace Kemper
Abstract : Background: Topical vancomycin may be an effective intervention to decrease the risk of postoperative surgical site infections (SSIs). The primary objective of this study was to evaluate the impact of topical vancomycin with intravenous (IV) cefazolin compared with IV cefazolin alone on the incidence of SSI in instrumented multilevel spinal fusion (MLSF) surgery. Methods: This was a retrospective cohort study of patients 18 years and older who underwent instrumented MLSF surgery between January 1, 2010, and July 31, 2014. Patients who underwent anterior cervical diskectomy and fusion, had spine surgery within 3 months prior to index case, received antibiotics other than IV cefazolin prior to surgery, or had preoperative length of stay longer than 5 days were excluded. SSIs were identified using Centers for Disease Control and Prevention National Healthcare Safety Network definitions. Summary statistics were computed. Variables found to be associated with increased risk of SSI through univariate analysis were included in a multivariate analysis. Results: Among 326 patients, 29 (8.9%) developed an SSI. Univariate analysis showed a trend toward decreased SSI incidence in the cohort receiving topical vancomycin with IV cefazolin compared with IV cefazolin alone, although this was not statistically significant ([6/116] 5.2% vs [23/210] 11.0%, p = 0.08). Topical vancomycin was associated with a protective effect against SSI in the multivariate analysis (odds ratio [OR] 0.26, p = 0.02). Significant risk factors for the development of SSI included female sex (OR 3.3, p = 0.01), increasing invasiveness score (p < 0.01), and diabetes mellitus (OR 5.1, p < 0.01). Conclusion: Topical vancomycin administered in addition to IV cefazolin was associated with a decreased risk of SSI in high‐risk MLSF patients. Female patients and those with diabetes mellitus were at higher risk of developing postsurgical infection. Further prospective studies are needed to confirm these results and to define the most clinically effective dose of topical vancomycin in this patient population.